Manajemen Pembelajaran Kitab Kuning untuk Mengembangkan Kemampuan Memaknai Al-Qur’an - Nuryana, Nuryana; Sukandar, Ahmad; Setiawan, Marwan (CV. Media Publikasi Profesional, 2022)
The Yellow Book Learning Management applied at the Al-Qur'an Al-Furqon Islamic Boarding School which in fact is an Islamic boarding school that still maintains the salafiyyah tradition and has not in detail implemented the Yellow Book Learning Management pattern to develop the ability to systematically recite the Qur'an. The purpose of this study was to determine the natural setting of the Al-Quran Al-Furqon Islamic Boarding School, the planning of the yellow book learning, the implementation of the yellow book learning, and the evaluation of the yellow book learning. The theory used in this research is learning management according to Davis in Haerana namely, learning management in four functions, namely planning, organizing, leading and controlling. The teacher's role in carrying out the learning management function is very basic, so that the teacher in the learning process is a manager because the teacher is in charge of preparing, organizing, implementing and conducting learning assessments. The method used in this research is qualitative with a case study approach. Data collection techniques include observation, interviews and documentation studies. Data analysis was carried out by categorizing data and interpreting data. The validity test of the data was carried out by extending participation, persistence of observation, triangulation, peer checks, negative case analysis, adequacy of references, detailed descriptions and auditing. The results of this study concluded that, Management of the Yellow Book Learning To Develop Al-Qur'an Recitation Ability in Al-Qur'an Al-Furqon Islamic Boarding Schools can be described from planning, implementation and evaluation. Learning planning at the Al-Furqon Islamic boarding school is rooted in the ability of the students themselves, if the students are still unfamiliar with the knowledge of their pesantren in learning books, they are adjusted to be oriented to study the books from the basic to the highest. The implementation of the yellow book learning at the Al-furqon Islamic boarding school is divided into two classical systems, namely ibtida/tsanawi. Evaluation of the yellow book learning in the Al-Qur'an Al-Furqon Islamic boarding school is oriented to the completeness of the material, one book is studied continuously and repeatedly until finally the students understand the content and content of the book they are studying with the sorogan, bandongan and rote system.